Casting of AA 7075 Aluminium Alloy into Gravity Die and Effect of the Die Preheating Temperature on Microstructure and Mechanical Properties - Hakan Gökmeşe*; Şaban Bülbül; Onur Gök (Tehnički Vjesnik, 2021)
In this study, light alloy casting technology, which has an important part in gravity die casting applications, was investigated. For this purpose, casting tests were conducted after the modelling and analysis studies of metal tensile bar die at 100 °C - 150 °C - 200 °C preheating temperatures by using finite element analysis method. Casting tests of AA 7075 aluminium alloy into gravity die were carried out at 800 °C and under different die preheating temperatures. After the casting process, tensile test measurements and hardness measurements of the test samples were made by preparing the tensile bars. Hardness measurements were performed before and after aging heat treatment (120 °C - 1440 minutes) as both macrohardness and microhardness. SEM and EDS analyses were performed for the microstructure and fracture surface examinations of the test samples. It was determined with modelling and analysis studies that increasing die preheating temperature increased the thermal stress and deformation and the highest percent elongation was 4.85% in terms of tensile properties. The hardness value before and after the aging heat treatment showed a decreasing tendency depending on increasing die preheating temperature.